1998
DOI: 10.1103/physrevb.57.6534
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between atomic-scale structure and mobility anisotropy inInAs/Ga1x

Abstract: We have performed detailed characterization of atomic-scale interface structure in InAs/Ga 1Ϫx In x Sb superlattices using cross-sectional scanning tunneling microscopy ͑STM͒ and established a semiquantitative correlation between interface structure and transport properties in these structures. Quantitative analysis of STM images of both ͑110͒ and (110) cross-sectional planes of the superlattice indicates that interfaces in the (110) plane exhibit a higher degree of interface roughness than those in the ͑110͒ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…The strikingly short correlation lengths we observe, relative to the findings of Lew et al 26 and Feenstra and co-workers, 15-17 suggest a simple mechanism for the generation of interfacial roughness in these structures that is directly related to the use of MEE to form the interfaces. Each InGaSb-on-InAs interface in these samples was formed by terminating the InAs layer with a monolayer of In followed by an Sb soak.…”
Section: A Interfacial Roughnesssupporting
confidence: 43%
See 1 more Smart Citation
“…The strikingly short correlation lengths we observe, relative to the findings of Lew et al 26 and Feenstra and co-workers, 15-17 suggest a simple mechanism for the generation of interfacial roughness in these structures that is directly related to the use of MEE to form the interfaces. Each InGaSb-on-InAs interface in these samples was formed by terminating the InAs layer with a monolayer of In followed by an Sb soak.…”
Section: A Interfacial Roughnesssupporting
confidence: 43%
“…Lew et al 26 found that the InAs-on-InGaSb interfaces were significantly rougher than the InGaSb-on-InAs ones in In 0.25 Ga 0.75 Sb/InAs superlattices grown at 380°C. In contrast, Feenstra and co-workers [15][16][17] observed the reverse to be true for InAs/ GaSb multilayers grown at 380°C: their InAs-on-GaSb interfaces were found to be smoother than GaSb-on-InAs interfaces.…”
Section: A Interfacial Roughnessmentioning
confidence: 99%
“…In a GaInSb/InAs superlattice, InSb-like bonds can be formed at the GaInSb-on-InAs interface by appropriately controlling the anion exchange. This is desirable, because InSb-like bonds at the interface offer superior structural and electronic properties [7][8][9]. More recently, Kaspi et al reported excellent structural and optical properties in an InAs/GaSb superlattice structure [40], which was grown in such a manner that InSb-like bonds were formed at the GaSb-on-InAs interfaces, while GaSb-like bonds were formed at the InAs-onGaSb interfaces by As/Sb exchange [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…1 At least two distinctive features of these reconstructions could potentially affect epitaxial growth: ͑1͒ they are structurally anisotropic, a consequence of the tetrahedral bonding and the zinc-blende crystal structure; and ͑2͒ they occur with a wide range of III/V stoichiometries, both less than and greater than unity. There is theoretical 2,3 and experimental [4][5][6][7] evidence that the structural anisotropy does, in fact, affect nucleation and growth during both homo-and heteroepitaxy, in part by causing surface diffusion to be anisotropic. The structural anisotropy also plays an important role in compositional modulation and ordering in III-V alloys ͑such as GaInP͒.…”
mentioning
confidence: 99%
“…It is well known that the interfacial disorder that may result, due to morphological roughness or intermixing, can cause observable effects on the properties of electronic and optical devices. Recent examples of such effects directly attributed to interface quality include an anisotropic reduction in mobility observed in InAs/GaInSb superlattices, 6 and a growth-temperature-dependent reduction in photoluminescence intensity in infrared laser structures. 10 Devices utilizing layers only a few monolayers thick, such as resonant tunneling diodes ͑RTDs͒, are expected to be particularly sensitive to these growth anomalies.…”
mentioning
confidence: 99%